CNN - Business Asia
CNN business magazine by journalist Stuart Varney who reports on: Asia’s business market and the technological competition between U.S. and Asian manufacturers; currency and stock markets in the world; trade deficit in the U.S.; Burmese and Thai drug trafficking; aging population in Japan; nuclear testing in Japan.